Mapping More Than Aboriginal Studies: Pedagogy, Professional Practice and Knowledge - Heidi Norman (The Australian Journal of Indigenous Education, 2014)
As undergraduate curriculum is increasingly required to meet a range of intellectual, professional practice and personal learning outcomes, what purpose does Australian Aboriginal Studies have in curriculum? Most Australian universities are currently in the process of developing institution-wide approaches to Indigenous Australian content in undergraduate curricula. One Australian university began this task by mapping how, where and why Indigenous perspectives, issues and content are included in undergraduate curriculum. This article reports on the findings of the mapping of Indigenous content and approaches to teaching at the University of Technology, Sydney (UTS) and thereby contributes to a strengths-based approach to understanding the purpose of Indigenous perspectives and issues in undergraduate curricula.